Liver Bleeding Due to HELLP Syndrome Treated With Embolization and Liver Transplantation: A Case Report and Review of the Literature - Messina, Valentina; Dondossola, Daniele; Paleari, Maria Chiara; Fornoni, Gianluca; Tubiolo, Daniela; Vergani, Patrizia; Rona, Roberto; Rossi, Giorgio (Frontiers in Surgery, 2021)
Background: Liver bleeding secondary to Elevated Liver enzymes and Low Platelet count (HELLP) Syndrome is an uncommon, but life-threatening peri-partum condition that needs a prompt multidisciplinary approach. Case presentation: Here we present a case of 28 years old pregnant woman, who presented to the obstetrics department with signs of preeclampsia and foetal growth restriction. An emergency caesarean section was performed and the patient developed a HELLP syndrome complicated by spontaneous liver rupture. After radiological and surgical procedures, liver failure became evident and a liver transplantation was successfully performed. The patient and her daughter are now alive. Conclusions: Despite the rarity of this disease, liver complications due to HELLP syndrome must be properly diagnosed and treated given the gravity of the possible evolution in young women. After diagnosis, the patients must be treated in specialized centres with gynecological, liver surgery and transplant skills.